Peran Musyawarah Guru Mata Pelajaran (MGMP) Pendidikan Agama Islam (PAI) Sekolah Menengah Kejuruan (SMK)Dalam Meningkatkan Kompetensi Profesional Guru di Kabupaten Jeneponto - Muzakkir, Muzakkir; Malli, Rusli; Sumiati, Sumiati (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study discusses the role of the Islamic Education Subject Teachers’ Forum (MGMP PAI) for vocational high schools (SMK) in Jeneponto Regency in enhancing teachers’ professional competence. The objectives are to: (1) examine the existence of MGMP PAI SMK in Jeneponto, (2) analyze its role in improving professional competence of teachers, and (3) identify supporting and inhibiting factors in carrying out that role. This is a field research study using a descriptive qualitative approach. Primary data were obtained from MGMP PAI SMK administrators, Islamic education teachers, and the Head of Islamic Education Section at the Ministry of Religious Affairs Office in Jeneponto. Secondary data came from relevant documents. Data collection techniques included observation, interviews, and documentation, and data validity was tested through triangulation. The findings reveal that MGMP PAI SMK in Jeneponto has existed since 2015 and is officially recognized, as evidenced by a formal decree. Its presence is perceived positively through various beneficial activities for members. MGMP plays a strategic role in developing professional competence by motivating teachers to improve their conceptual understanding, organize subject structures, systematize content, and design effective lesson plans aligned with student needs. Supporting factors include internal strengths such as active involvement of members and external opportunities through partnerships. Inhibiting factors include lack of motivation among members, their workload in home institutions, limited facilities, and budget constraints. This study is expected to contribute to strengthening the existence and innovation of MGMP PAI SMK in fostering the professional development of Islamic education teachers.